Data for: High resolution seasonal and decadal inventory of anthropic gas-phase and particle emissions for Argentina - Puliafito, Salvador Enrique (2022)
This Dataset support the gas-phase and particulate atmospheric emission inventory for Argentina in high spatial resolution (approx. 2.5 km × 2.5 km). This dataset includes the latest revision version of the GEAA-AEIv3.0M inventory. Monthly pollutant emission maps for CO2, CH4, N2O, CO, NOx, NMVOC, NH3, SO2, PM10, PM2.5, TSP and BC between 1995 and 2020 are provided. The emission inventory includes the following sectors: energy production, fugitive emissions from oil and gas production, industrial fuel consumption and production, transport (road, maritime and air), agriculture, livestock production, residential, commercial and biomass burning. The whole dataset has been developed with the porpoise of contributing to various areas of research and governmental assessments, including air quality modeling and decision making, among others.